2008
DOI: 10.4141/cjas07074
|View full text |Cite
|
Sign up to set email alerts
|

Review: Current knowledge on mammary blood flow, mammary uptake of energetic precursors and their effects on sow milk yield

Abstract: Review: Current knowledge on mammary blood flow, mammary uptake of energetic precursors and their effects on sow milk yield. Can. J. Anim. Sci. 88: 195Á204. Dietary availability of nutrients to the mammary gland is a major limiting factor for sow milking potential. Nutrient availability to the udder is estimated by measuring mammary arteriovenous differences, which are affected by blood flow as well as circulating concentrations of nutrients. Mammary blood flow can be measured either directly or indirectly. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 37 publications
0
25
0
2
Order By: Relevance
“…Metabolic adaptations such as a progressive decrease in insulin sensitivity during late gestation and lactation or an increased sow catabolism during lactation (Valros et al, 2003) allow the provision of glucose to the pregnant uterus (Père et al, 2000) or the mammary gland Farmer et al, 2008). Indeed, glucose is the main energetic fuel for metabolism and growth of the foetuses (Père, 2001(Père, , 2003, and for milk synthesis (Farmer et al, 2008). The transition between gestation and lactation involves rapid and important changes in numerous hormones and metabolites and may interfere on the metabolic status of the sow during further lactation.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic adaptations such as a progressive decrease in insulin sensitivity during late gestation and lactation or an increased sow catabolism during lactation (Valros et al, 2003) allow the provision of glucose to the pregnant uterus (Père et al, 2000) or the mammary gland Farmer et al, 2008). Indeed, glucose is the main energetic fuel for metabolism and growth of the foetuses (Père, 2001(Père, , 2003, and for milk synthesis (Farmer et al, 2008). The transition between gestation and lactation involves rapid and important changes in numerous hormones and metabolites and may interfere on the metabolic status of the sow during further lactation.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological hypophagia that occurs in sows during lactation is established immediately after farrowing as a consequence of a high concentration of blood glucose from day 85 of gestation (Pére & Etienne, 2007;Mosnier et al, 2010). Before farrowing, the physiological objective is to provide energy to the foetuses for their growth during the last third of gestation (Farmer et al, 2008). After farrowing, high concentrations of blood glucose are maintained to supply energy requirements for synthesis and milk production during lactation (Bergsma et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…This was a larger quantity of milk than was produced by the CG sows, but was similar to that observed in EG. However, these differences among studies in milk production are possibly attributable to differences in the genetic material and the environment (Farmer et al, 2008). In contrast, Thingnes et al (2012) suggested that additional feed intake by the sows during lactation is not reflected in milk production, but is used to reduce weight loss.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because no other studies are available to compare the plasma flow estimated with calcium, it is unknown whether calcium is a valid marker. Unlike amino acids, calcium is not metabolized hence (Farmer et al, 2008b). Guan et al (2004a) Fick (lysine) 11 4.5 11.4 560 Guan et al (2004b) Fick (lysine) 11 3.6 10.7 490 Linzell et al (1969a) 2 Fick ( 3 HO) 6 1.9 3 6.2 441 3 Nielsen et al 2002bFick (lysine) 8 3.2 10 550 Nielsen et al 2002aFick (lysine) 12 5.5 7.4 1,050 Nielsen et al (2002a) Fick (methionine) 12 4.4 7.4 858 Nielsen et al (2002a) Fick (calcium) 12 2.8 7.4 548 Renaudeau et al (2002) Flow probe 12 3.6 3 11 471 3 Renaudeau et al 2002Fick (lysine) 12 3.9 4 11 511 Trottier et al (1997) Fick (lysine) 11 3.0 8.1 541…”
Section: Estimating Mammary Blood Flowmentioning
confidence: 99%